2003
DOI: 10.1099/mic.0.25993-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two specific regulatory Aspergillus niger mutants shows antagonistic regulation of arabinan and xylan metabolism

Abstract: This paper describes two Aspergillus niger mutants (araA and araB) specifically disturbed in the regulation of the arabinanase system in response to the presence of L-arabinose. Expression of the three known L-arabinose-induced arabinanolytic genes, abfA, abfB and abnA, was substantially decreased or absent in the araA and araB strains compared to the wild-type when incubated in the presence of L-arabinose or L-arabitol. In addition, the intracellular activities of L-arabitol dehydrogenase and L-arabinose redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 26 publications
6
46
2
Order By: Relevance
“…Since xyl1 is dispensable for growth on L-arabinitol, this effect must therefore be a regulatory one. De Groot et al (8) reported that the induction of arabinan-degrading enzymes by L-arabinitol in A. niger depends on the function of the products of the araA and araB genes, which positively regulate their expression and also that of the genes encoding the L-arabinose catabolic pathway. Unfortunately, the respective genes have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since xyl1 is dispensable for growth on L-arabinitol, this effect must therefore be a regulatory one. De Groot et al (8) reported that the induction of arabinan-degrading enzymes by L-arabinitol in A. niger depends on the function of the products of the araA and araB genes, which positively regulate their expression and also that of the genes encoding the L-arabinose catabolic pathway. Unfortunately, the respective genes have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…(for a review, see reference 43). However, XlnR has been reported not to regulate arabinan and L-arabinose metabolism in the Aspergilli (8). In analogy, Stricker et al (42) reported that a xyr1 knock out in H. jecorina did not affect growth of the fungus on L-arabinose and also L-arabinose reductase activities.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…During fermentation of molasses, glucose is consumed first, followed by fructose and sucrose (Rincon et al 2001). Catabolic repression by glucose and fructose (de Groot et al 2003) does not permit the formation of extracellular invertases, which converts sucrose into glucose and fructose, which are then sequentially consumed by the organism.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated whether the mutant selection system used by de Groot et al (2003) could be applied to identify functions involved in xylitol metabolism. We show that this selection system was capable of selecting a new mutant affected in xylitol-mediated repression, and detailed investigation of a xylitol-derepressed mutant shows it to be severely hampered in xylitol transport.…”
Section: Introductionmentioning
confidence: 99%